EXTENSION IN THE SHELF LIFE OF SHRIMP (PENAEUS MERGUIENSIS ) USING CELL FREE SUPERNATANT OF LACTIC CULTURE (Biological Sciences - PJSIR, 2001)
Changes in the sensory quality of raw and cooked shrimp Penaeus merguiensis, total bacterial counts, total volatile bases (TVB) and pH were determined in shrimp treated with the lactic culture. The sensory score point averages of treated and untreated samples were found significantly different (p values 0.014 and 0.042 for raw and cooked shrimp, respectively) . The average initial bacterial load of fresh shrimp decreased immediately after treatment with the lactic culture. During ice storage, the counts i ncreased with time in the treated samples as compared to the control. Statistical analyses showed significant differences in the counts of treated and untreated samples (p value 0.021) during the storage period . The pH increased with time and reached to 7.43 and 7.85 in treated and untreated samples, respectively. The shelflife of the treated samples was extended, at least, by one week.